Track-before-Detect Using Swerling 0, 1, and 3 Target Models for Small Manoeuvring Maritime Targets. (15th May 2008) - McDonald McDonald, Michael Michael; Balaji Balaji, Bhashyam Bhashyam
Abstract : Real-radar data containing a small manoeuvring boat in sea clutter is processed using a finite difference (FD) implementation of continuous-discrete filtering with a four-dimensional constant velocity model. Measurement data is modelled assuming a Rayleigh sea clutter model with embedded Swerling 0, 1, or 3 target signal models. The results are examined to obtain a qualitative understanding of the effects of using the different target models. The Swerling 0 model is observed to exhibit a heightened sensitivity to changes in measured signal strength and provides enhanced detection of the maritime target examined at the cost of more peaked or multimodal posterior density in comparison with Swerling 1 and 3 targets.